A hyperbranched fluorescent supramolecular polymer with aggregation induced emission (AIE) properties. Issue 26 (6th June 2016) - Zhang, Jing; Zhu, Jiachen; Lu, Chenjie; Gu, Zhengye; He, Tian; Yang, Anle; Qiu, Huayu; Zhang, Mingming; Yin, Shouchun
Abstract : A hyperbranched fluorescent supramolecular polymer with aggregation induced emission properties was prepared by orthogonal assembly of host–guest and metal–ligand interactions. Abstract : A hyperbranched fluorescent supramolecular polymer with aggregation induced emission properties was constructed by the orthogonal assembly of host–guest and metal–ligand interactions.